A plastid‐localized bona fide geranylgeranyl diphosphate synthase plays a necessary role in monoterpene indole alkaloid biosynthesis in Catharanthus roseus. (10th April 2020) - Kumar, Sarma Rajeev; Rai, Avanish; Bomzan, Dikki Pedenla; Kumar, Krishna; Hemmerlin, Andréa; Dwivedi, Varun; Godbole, Rucha C.; Barvkar, Vitthal; Shanker, Karuna; Shilpashree, H. B.; Bhattacharya, Ankita; Smitha, Attibele Ramamurthy; et al.
SUMMARY: In plants, geranylgeranyl diphosphate (GGPP, C20 ) synthesized by GGPP synthase (GGPPS) serves as precursor for vital metabolic branches including specialized metabolites. Here, we report the characterization of a GGPPS (CrGGPPS2) from the Madagascar periwinkle ( Catharanthus roseus ) and demonstrate its role in monoterpene (C10 )‐indole alkaloids (MIA) biosynthesis. The expression of CrGGPPS2 was not induced in response to methyl jasmonate (MeJA), and was similar to the gene encoding type‐I protein geranylgeranyltransferase_β subunit ( CrPGGT‐I_β ), which modulates MIA formation in C. roseus cell cultures. Recombinant CrGGPPS2 exhibited a bona fide GGPPS activity by catalyzing the formation of GGPP as the sole product. Co‐localization of fluorescent protein fusions clearly showed CrGGPPS2 was targeted to plastids. Downregulation of CrGGPPS2 by virus‐induced gene silencing (VIGS) significantly decreased the expression of transcription factors and pathway genes related to MIA biosynthesis, resulting in reduced MIA. Chemical complementation of CrGGPPS2‐ vigs leaves with geranylgeraniol (GGol, alcoholic form of GGPP) restored the negative effects of CrGGPPS2 silencing on MIA biosynthesis. In contrast to VIGS, transient and stable overexpression of CrGGPPS2 enhanced the MIA biosynthesis. Interestingly, VIGS and transgenic‐overexpression of CrGGPPS2 had no effect on the main GGPP‐derived metabolites, cholorophylls and carotenoids in C. roseus leaves. Moreover, silencing of CrPGGT‐I_β, similar to CrGGPPS2‐ vigs, negatively affected the genes related to MIA biosynthesis resulting in reduced MIA. Overall, this study demonstrated that plastidial CrGGPPS2 plays an indirect but necessary role in MIA biosynthesis. We propose that CrGGPPS2 might be involved in providing GGPP for modifying proteins of the signaling pathway involved in MIA biosynthesis. Significance Statement: Our study reveals a link between C20 metabolic intermediate (GGPP) and (C10 )‐monoterpene indole alkaloids (MIA), thus adding new insights into MIA formation in Catharanthus roseus . The findings demonstrate that the plastid‐localized bona fide CrGGPPS2 plays an important role in MIA biosynthesis through its potential involvement in providing the precursor for protein‐geranylgeranyl‐transferase (PGGT) involved in modulation of the MIA pathway